2015
DOI: 10.1071/wf13152
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between annual plant productivity, nitrogen deposition and fire size in low-elevation California desert scrub

Abstract: Abstract. Although precipitation is correlated with fire size in desert ecosystems and is typically used as an indirect surrogate for fine fuel load, a direct link between fine fuel biomass and fire size has not been established. In addition, nitrogen (N) deposition can affect fire risk through its fertilisation effect on fine fuel production. In this study, we examine the relationships between fire size and precipitation, N deposition and biomass with emphasis on identifying biomass and N deposition threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…It should be pointed out that the situations we have modeled probably represent conditions where fire will not spread extensively, since the conditions producing the greatest amount of biomass in our experiments yield a biomass threshold of approximately 33 g m −2 for the open (OF) matrix habitat (Table 3; Mojave-2013 High Precipitation Experiment). In contrast, published estimates of the threshold values for carrying fire in grass-dominated systems have been reported to be between 70 and 150 g m −2 (see Rao et al, 2015), at least double the maximum value we observed. The Rao et al's (2015) paper, which is a modeling study of fire size as a function of precipitation, N loading and biomass productivity in low-elevation desert scrub, found that there was no distinct biomass threshold that would produce extensive fires.…”
Section: Implications For Fire Managementcontrasting
confidence: 82%
“…It should be pointed out that the situations we have modeled probably represent conditions where fire will not spread extensively, since the conditions producing the greatest amount of biomass in our experiments yield a biomass threshold of approximately 33 g m −2 for the open (OF) matrix habitat (Table 3; Mojave-2013 High Precipitation Experiment). In contrast, published estimates of the threshold values for carrying fire in grass-dominated systems have been reported to be between 70 and 150 g m −2 (see Rao et al, 2015), at least double the maximum value we observed. The Rao et al's (2015) paper, which is a modeling study of fire size as a function of precipitation, N loading and biomass productivity in low-elevation desert scrub, found that there was no distinct biomass threshold that would produce extensive fires.…”
Section: Implications For Fire Managementcontrasting
confidence: 82%
“…There is evidence of interactions between N and burning. In Californian desert shrublands, elevated N deposition is suggested to increase fire frequency (Rao et al, 2015).…”
Section: Burningmentioning
confidence: 99%
“…Long-term reductions in resistance to invasion can be caused by repeated fires at higher elevations, or even single fires at lower elevations (Klinger and Brooks, 2017). Also, atmospheric nitrogen deposition downwind of urban or agricultural areas can increase soil nitrogen availability and biomass of invasive annual grasses and may elevate the potential for fire, and invasive grass dominance (Brooks, 2003;Allen et al, 2009;Rao and Allen, 2010;Rao et al, 2014).…”
Section: Resistance To Invasionmentioning
confidence: 99%